Dihydrotestosterone regulates oxidative stress and immunosuppressive cytokines in a female BALB/c mouse model of Graves' disease - Fengyi Zhao; Liping Wu; Yue Wang; Lianye Liu; Fei Yang; Yushi Sun; Xiang Jiao; Lingyu Bao; Pu Chen; Qiangrong Liang; Bingyin Shi (Taylor & Francis Group, 2019)
Background: Graves' disease (GD) is an autoimmune disease that affects more women than men. In our previous study, a potent bioactive androgen, 5α-dihydrotestosterone (DHT) showed a protective effect against GD in female BALB/c mice. Evidence indicates that abnormal oxidative stress and immunosuppressive cytokines (TGF-β, IL-35) play critical roles in the pathogenesis and development of GD. The purpose of this research is to measure these cytokines and oxidative stress markers to explore potential protective mechanisms of DHT in a BALB/c mouse model of GD. Methods: GD was induced in female BALB/c mice by intramuscular injection of an adenovirus expressing the A-subunit of the TSH receptor (Ad-TSHR289). DHT or a matching placebo was injected every 3 days. Mice were sacrificed four weeks after the third virus immunization to obtain blood, thyroid and spleen for further analysis. Results: Thyroid hormones were significantly reduced in DHT treated GD mice. In addition, DHT attenuated thyroid oxidative injuries in GD mice, as shown by decreased total antioxidation capability (TAOC), superoxide dismutase (SOD) and the level of malondialdehyde (MDA). The levels of immunosuppressive cytokines (TGF-β, IL-35) in DHT group were significant higher compared with the GD group. Conclusions: The results demonstrated that DHT could reduce the severity of GD in female BALB/c mice by regulating oxidative stress. The upregulation of immunosuppressive cytokines might be another important protective mechanism.